The Effect of Technology Implementation, Organizational Commitment, And Employee Competence on Employee Performance with Job Satisfaction as a Moderating Variable (A Case Study of District Offices in Tegal City) - Ahmad Faozi; Dien Noviany Rahmatika; Dewi Indriasih (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of technology implementation, organizational commitment, and employee competence on employee performance at district offices in Tegal City, with job satisfaction as a moderator. Questionnaire data were collected from all 240 employees through saturated sampling and analyzed using SmartPLS 4. Technology implementation, employee competence, and job satisfaction positively affect performance, whereas organizational commitment has no significant effect. Job satisfaction strengthens the effects of technology implementation and employee competence but does not moderate the effect of organizational commitment. The model explains 81.1% performance variance, providing practical guidance for improving public-sector employee performance. Keywords: Technology Implementation; Organizational Commitment; Employee Competence; Job Satisfaction; Employee Performance; Public Sector; PLS-SEM